Creation and implementation of the SIENMECRO Chronic Patient Drug Delivery System: qualitative study - Llanos-Zavalaga, Luis Fernando (2023)
Introduction: Faced with the pandemic produced by SARS-CoV-2, the Peruvian government implemented several measures such as the temporary closure of primary care facilities and the health system implemented various policies and strategies; one of them was to create and implement the Drug Delivery System for Chronic Patients (SIENMECRO) project. Objective: To describe the creation and implementation process of SIENMECRO project. Methods: Qualitative case study that involved reviewing existing documentation such as texts and videos and conducting in-depth interviews with officials and collaborators involved since the preparation of SIENMECRO proposal. Results: SIENMECRO project emerges as a positive initiative with the aspiration of promoting an integrated health system that addresses the health reality from the social determinants of health, due to patients’ difficulties to go to their controls and to receive their treatment. Although there was no comprehensive plan for the implementation and control of the project, it was essential to cover the need for health care for a vulnerable segment of the population, avoiding their transfer and preserving the health of the people most likely to suffer complications from COVID-19 infection. Conclusions: It is an initiative where the health system takes a more proactive role for the benefit of the population, implementing the use of technology of the information and communication in health care, articulating with the various providers and bringing services closer to the most vulnerable citizens.